Pilot study on the effects of a 2-week hiking vacation at moderate versus low altitude on plasma parameters of carbohydrate and lipid metabolism in patients with metabolic syndrome - Gutwenger, Ivana; Hofer, Georg; Gutwenger, Anna K; Sandri, Marco; Wiedermann, Christian J (BMC research notes, 2015)
Background Hypoxic and hypobaric conditions may augment the beneficial influence of training on cardiovascular risk factors. This pilot study aimed to explore for effects of a two-week hiking vacation at moderate versus low altitude on adipokines and parameters of carbohydrate and lipid metabolism in patients with metabolic syndrome. Methods Fourteen subjects (mean age: 55.8 years, range: 39 – 69) with metabolic syndrome participated in a 2-week structured training program (3 hours of guided daily hiking 4 times a week, training intensity at 55-65% of individual maximal heart rate; total training time, 24 hours). Participants were divided for residence and training into two groups, one at moderate altitude (1,900 m; n = 8), and the other at low altitude (300 m; n = 6). Anthropometric, cardiovascular and metabolic parameters were measured before and after the training period. Results In study participants, training overall reduced circulating levels of total cholesterol (p = 0.024), low-density lipoprotein cholesterol (p = 0.025) and adiponectin (p < 0.001). In the group training at moderate altitude (n = 8), lowering effects on circulating levels were significant not only for total cholesterol, low-density-lipoprotein cholesterol and adiponectin (all, p < 0.05) but also for triglycerides (p = 0.025) and leptin (p = 0.015), whereas in the low altitude group (n = 6), none of the lipid parameters was significantly changed (each p > 0.05). Hiking-induced relative changes of triglyceride levels were positively associated with reductions in leptin levels (p = 0.006). As compared to 300 m altitude, training at 1,900 m showed borderline significant differences in the pre-post mean reduction rates of triglyceride (p = 0.050) and leptin levels (p = 0.093). Conclusions Preliminary data on patients with metabolic syndrome suggest that a 2-week hiking vacation at moderate altitude may be more beneficial for adipokines and parameters of lipid metabolism than training at low altitude. In order to draw firm conclusions regarding better corrections of dyslipidemia and metabolic syndrome by physical exercise under mild hypobaric and hypoxic conditions, a sufficiently powered randomized clinical trial appears warranted. Trial registration ClinicalTrials.gov ID NCT02013947 (first received November 6, 2013).